ŞİİR, DİL, TAKLİT VE İNTİHAL ÜZERİNE - (:unkn) unknown (My University, 2014)
0

T.S. Eliot state precisely that the fact that poetry is based more on feelings than on thought makes is among the most national arts. Accepting Eliot’s idea that poetry is an art of language and that we can thing in a foreign language when we can only feel in our mother tongue, we can say that Turkish poetry has been in an impass since its beginnings. Some people would go so far as to say that our poetry has never been able to cross the threshold of imitation and all of this, since the time Divan poetry. Did not even poets like Baki and Fuzulî rival Persian poets without stopping ? Wasn’t the fact that our poetry was abandoned during the period of Tanzimat and Servet-i Fünun Persia for Europe, more precisely France, the precursive sign of a new epoque of imitation ? Nevertheless, imitation in art is an inevitable pheonomenon and universally known. Every artist, as one goes along his progression faces this imitation process, and this is a crutial stage of his improvement. Therefore, this process sould not be confused with thievery. The literary thievery is an act which is more or less tolerated and chat we gently name « plagiary ». So, the fact chat a paet «borrows» to another some lines can be somehow tolerable. However, if we should come back to Eliot’s logic, this borrowing should be restrained only within the framework of a some language
ON POETRY, LANGUAGE, IMMITATION AND PLAGIARISM
Keywords: Dil ve Dil Bilim